Incorporation of molybdenum(vi) in akaganéite (β-FeOOH) and the microbial reduction of Mo–akaganéite by Shewanella loihica PV-4. Issue 41 (11th October 2017) - Bolanz, Ralph M.; Grauer, Christoph; Cooper, Rebecca E.; Göttlicher, Jörg; Steininger, Ralph; Perry, Stephen; Küsel, Kirsten
Abstract : Among all highly-crystalline iron oxides present in the environment, akaganéite (β-FeO(OH, Cl)) possesses one of the most unconventional structural setups and is a known scavenger for large quantitates of molybdenum (Mo 6+ ). Abstract : Among all highly-crystalline iron oxides present in the environment, akaganéite (β-FeO(OH, Cl)) possesses one of the most unconventional structural setups and is a known scavenger for large quantitates of molybdenum (Mo 6+ ). The factors controlling the exact mechanism for Mo 6+ incorporation into the akaganéite crystal structure are poorly understood and the ability of dissimilatory Fe(iii )-reducing microorganisms to reduce pure akaganéite or Mo-carrying iron oxides is not well characterized. In the current study, we investigated the short-range order around Mo 6+ in akaganéite and the fate of Mo 6+ under microbially-mediated Fe(iii )-reducing conditions. We found that akaganéite can incorporate up to 14.11 ± 0.22 wt% Mo, while the Fe content decreases from 59.70 ± 0.31 to 40.40 ± 0.24 wt%, which indicates a loss of 2–3 Fe atoms for each Mo incorporated. Simultaneously, the crystal structure unit cell parameters a, b and c decrease, while β increases with increasing Mo content. Surprisingly, dissolution of akaganéite by Shewanella loihica PV-4 showed higher dissolution rates of Mo-bearing akaganéite compared to Mo-free akaganéite. Moreover, these results suggest the reduction of Mo 6+ is most likely microbially-induced (Fe 3+ → Fe 2+, Mo 6+ + 2Fe 2+ → Mo 4+ + 2Fe 3+ ). Furthermore, X-ray absorption spectra collected at the Mo L3 -edge show a peak-splitting of the white line with a splitting gap of 2.7 eV and an increased amplitude for the first peak. This observation indicates Mo 6+ is octahedrally coordinated by oxygen, assuming a strongly distorted MoO6 -octhaedron. Fitting of the short-range order around Mo 6+ in akaganéite supports the presence of a strongly distorted MoO6 -octahedron in a coordination environment similar to the Fe position in akaganéite and the formation of Fe-vacancies close to the newly incorporated Mo 6+ .